A review of complete albinism in bats with five new cases from Brazil - Uieda, W. (Polish Acad of Sciences, 2000)
Complete albinism is a rare phenomenon that occurs in all vertebrate groups. In bats, albinism has been recorded in several species but this information has not previously been reviewed in detail nor has there been an analysis of its importance. In this study, cases of albinism from the literature are checked and new cases are presented. Complete albinism in bats is documented in eight families, 38 species, and at least 64 individuals (47.4% female female and 52.6% males; n = 38). of these, 39 individuals were observed and/or captured in sheltered roosts, such as caves (51.3%), mines and galleries (20.5%), buildings (17.9%), and hollow-trees and bird boxes (7.7%). Only one albino bat (2.6%) was captured in an external roost (foliage). This individual is the fruit bat, Artibeus planirostris, which is recorded here for the first time. Information on four additional cases of albino individuals of the common vampire bat, Desmodus rotundus, is also presented. It is suggested that sheltered roosts favour survival of albino bars, offering protection against sunlight, water loss, and visually hunting predators.
Keywords: albinism; Desmodus rotundus; Artibeus planirostris; Brazil